THE IMPACT OF DISSENTING OPINION PHPU 2024 ON THE DEVELOPMENT OF LAW AND DEMOCRACY IN INDONESIA - Azis Rahman (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2024)
ABSTRACT This research discusses the dissenting opinion made by the three judges in the 2024 PHPU decision, as it is known that dissenting opinion is a difference of opinion of the judges, this dissenting opinion includes a description of the judge's argumentation in a particular case. Experts say that this dissenting opinion is an alternative to future legal reform, because it contains genuine ideas that are different from the nature of decisions which are sometimes still casuistic. This dissenting opinion is an interesting event in the 2024 PHPU dispute, looking at the judge's decision regarding the 2004 election dispute with the decision of the judges in seeking the election dispute decision process there is no difference, if they have not yet found a bright spot for different decisions, a RPH or Consultative Meeting of Judges is held, until they find a mutual agreement. Therefore, to answer these problems, this research comes by using library research. The essence of dissenting opinion cannot provide legal certainty because legal certainty basically has its products, there is a source and legal basis, but if legal certainty does not have legal force or legal basis, it is not legal certainty. The judge's dissenting opinion is in line with the principle of democracy which reflects the guarantee of the right to dissent in deciding a case. The right to dissent shows the existence of a legal system that respects pluralism and freedom of expression. Keywords: Legal certainty; Dissenting Opinion; Democracy.